Pembangunan Platform Sportify: Platform Pencari Teman Olahraga Berbasis Mobile Android - Agung Pramono; Fajar Pradana; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
An exercise is basically a very important requirement for every human being in life so that physical and health conditions can be maintained properly. But this one activity is very easy for us to leave with various pretexts. The lack of public interest in exercise can be influenced by a variety of things, including lack of players, inappropriate time, and the distance of distant sports venues. With the current large level of community penetration in using the internet coupled with a large number of smartphone ownership, this study made a solution in the form of a sports friend search platform called